2020
DOI: 10.1101/2020.06.30.179481
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SALL4 controls cell fate in response to DNA base composition

Abstract: AbstractMammalian genomes contain long domains with distinct average compositions of A/T versus G/C base pairs. In a screen for proteins that might interpret base composition by binding to AT-rich motifs, we identified the stem cell factor SALL4 which contains multiple zinc fingers. Mutation of the domain responsible for AT binding drastically reduced SALL4 genome occupancy and prematurely up-regulated genes in proportion to their AT content. Inactivation of this single AT-bind… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 90 publications
4
17
0
Order By: Relevance
“…Given that SALL4 ZFC1 binds to AT-rich DNAs weaker than SALL4 ZFC4 , it might be insufficient to maintain the occupancy of SALL4 after the deletion of ZFC4, consistent with previous report that mutation or deletion of SALL4 ZFC4 impairs the targeting of SALL4 at genome sites 14 .…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Given that SALL4 ZFC1 binds to AT-rich DNAs weaker than SALL4 ZFC4 , it might be insufficient to maintain the occupancy of SALL4 after the deletion of ZFC4, consistent with previous report that mutation or deletion of SALL4 ZFC4 impairs the targeting of SALL4 at genome sites 14 .…”
Section: Discussionsupporting
confidence: 89%
“…Very recently, two lines of work independently identified Spalt-like transcription factor 4 (SALL4) as the AT-rich DNA binding protein via pull-down mass spectrometry screen and protein binding microarray, respectively 14,15 . SALL4 belongs to the Spaltlike transcription factors (SALLs) family, which includes SALL1-4 16 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…unexplored. It was recently demonstrated that this transcription factor has affinity for AT-rich regions 48 , thus providing further support to the ARID1B-SALL4 interaction. SALL4 mutations are also associated with developmental syndromes, including Okihiro syndrome, Holt-Oram syndrome, and Townes-Brocks Syndrome 49 .…”
Section: The Arid1b-baf Complex Exclusively Incorporates Smarca4 As Atpase Subunitmentioning
confidence: 77%